-3(9+a)=33

Simple and best practice solution for -3(9+a)=33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(9+a)=33 equation:


Simplifying
-3(9 + a) = 33
(9 * -3 + a * -3) = 33
(-27 + -3a) = 33

Solving
-27 + -3a = 33

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '27' to each side of the equation.
-27 + 27 + -3a = 33 + 27

Combine like terms: -27 + 27 = 0
0 + -3a = 33 + 27
-3a = 33 + 27

Combine like terms: 33 + 27 = 60
-3a = 60

Divide each side by '-3'.
a = -20

Simplifying
a = -20

See similar equations:

| 8+11a=-234 | | B(3b-1)= | | 13m-7-10(3m+10)= | | 12x-118=138-4x | | -5(3x-9)+7=-15x+52 | | 6x+10=5(-2x+-4) | | 144+2x=64+22x | | 11111111111111116=5x | | 144+2x=64+22 | | -159-5x=12x+96 | | x+4(x+1)-2(x-3)=1 | | 6(3-t)=-27 | | -7a+9=49 | | -5=x-17 | | -185.00+35.00x=070.00-50.00x | | 5*2=9 | | 8r+7-6r-5= | | 4x+3(x-4)-(x+2)=6 | | 5p-25=2 | | F(4)=18x+14 | | 9s+4=148 | | 6-Y=11 | | -7x^2+3x=0 | | 6x-38=52+11x | | -2(3x-7)=6x+14 | | 3m^2+14m+58=0 | | -17r=102 | | -5-3(-6+x)-7x=-7 | | 2-4x=10x-28 | | 5x(x-6)=-50 | | 3(5x-1)-2(2x-18)=10x+6 | | 4x+-y=2 |

Equations solver categories